2021
DOI: 10.30650/jik.v9i1.2218
|View full text |Cite
|
Sign up to set email alerts
|

The RELATIONSHIP BETWEEN TYPES OF PLASMODIUM FALCIPARUM AND PLASMODIUM VIVAX WITH THE DEGREE OF THROMBOCYTOPENIA IN MALARIA PATIENTS AT RSUD RATU AJI PUTRI BOTUNG PENAJAM PASER UTARA

Abstract: ABSTRACT Malaria is a tropical infectious disease with high morbidity and mortality rates. In malaria, various kinds of haematological complications can arise, one of which is thrombocytopenia. Thrombocytopenia is most commonly encountered during acute malaria infection with varying degrees observed in both Plasmodium falciparum and Plasmodium vivax infections. The purpose of this study was to determine the relationship between the types of Plasmodium falciparum and Plasmodium vivax with the degree of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
0
0
Order By: Relevance
“…Suryadi et al discovered 310 cases of malaria, 60.3% of which were caused by Plasmodium falciparum and 39.7% by Plasmodium vivax in a hospital-based study. 22 The findings revealed that the communities' malaria knowledge was quite good. This is consistent with Lumolo et al's findings that public awareness of malaria is high (55.8%).…”
Section: Discussionmentioning
confidence: 96%
“…Suryadi et al discovered 310 cases of malaria, 60.3% of which were caused by Plasmodium falciparum and 39.7% by Plasmodium vivax in a hospital-based study. 22 The findings revealed that the communities' malaria knowledge was quite good. This is consistent with Lumolo et al's findings that public awareness of malaria is high (55.8%).…”
Section: Discussionmentioning
confidence: 96%